SIGLEC1 (CD169) is a sensitive biomarker for the deterioration of the clinical course in childhood systemic lupus erythematosus. (December 2020) - Stuckrad, Sae Lim von; Klotsche, Jens; Biesen, Robert; Lieber, Mareike; Thumfart, Julia; Meisel, Christian; Unterwalder, Nadine; Kallinich, Tilmann
Background: To analyse the validity of membrane-bound SIGLEC1 (CD169) as a sensitive biomarker for monitoring disease activity in pediatric systemic lupus erythematosus (SLE). Methods: 27 children and adolescents with SLE were followed for a mean of 13.5 months. During consecutive routine visits SLEDAI-2k, C3, C4 and ds-DNA values were determined. Additionally, expression of SIGLEC1 on monocytes was determined by flow cytometry. The amount of PE-labelled CD169 mAb bound per monocyte was analyzed using QuantiBRITE™ PE tubes. Associations between biomarkers and the clinical course were investigated by regression analysis. Results: In general, SIGLEC1 expression is high on SLE-derived monocytes (mean 6 359 (SD 6 056) molecules/monocyte, cut-off 2 500 molecules/monocyte), all patients with newly diagnosed SLE exhibit elevated expression (mean 13366 (SD 7 750) molecules/monocyte). Changes (Δ) in SIGLEC1 levels during the clinical course is the only biomarker that significantly correlates with the change in SLEDAI-2k (betaST  = 0.28, p = 0.001). At follow-up visit, a clinically important worsening was experienced by 47.6% of patients with a Δ SIGLEC1 > 2 151 molecules/cell (OR 5.31) and 72.4% with a Δ SIGLEC1 > 756 molecules/cell (OR 8.90). Conversely, 36.4% of patients with a Δ SIGLEC1 < -2 818 molecules/cell (OR 4.16, percentiles as cut-off criteria) and 50.0% of patients with a Δ SIGLEC1 < -1 370 molecules/cell (OR 3.55, application of Youden index) showed clinical improvement. SIGLEC1 expression correlates inversely with the amount of therapeutically applied hydroxychloroquine (p < 0.001). Conclusions: SIGLEC1 expression on monocytes is a sensitive biomarker for adjusting disease activity in childhood SLE and represents a promising and easily applicable tool for disease monitoring.